Democratic regression in comparative perspective: scope, methods, and causes. Issue 1 (2nd January 2021) - Diamond, Larry
ABSTRACT: Between 1974 and 2005, a majority of states became democratic for the first time in history. However, a global democratic recession began in 2006 and has persisted – and deepened – over the past 14 years. Not only have average levels of freedom (or democratic quality) been declining globally and in most parts of the world, but the pace of democratic breakdown accelerated and the number of democratic transitions declined, particularly in the past five years. Democratic regression is particularly visible among the G-20 countries and other most populous and geopolitically weighty countries, 19 of which have declined in freedom during the democratic recession, with only two improving. The principal method of democratic regression has been incremental strangulation of democracy by elected (typically populist) executives who gradually eviscerate institutional checks, political opposition, independent media, and other forces of scrutiny and resistance in civil society. Weak and declining rule of law has predisposed regimes to democratic regression, enabling ambitious rulers to hollow out political competition. But international factors have also been crucial, generating common economic and social stresses while lifting the constraints and lowering the risks autocrats face as they inaugurate or accelerate the slide into authoritarianism.